On the fine edge of the real and the fictional - Sarbadhikary, Krishna (1999)
An examination of literary representations of women of age in stories from different social class, cuslture, economic and religious backgrounds in stories written by women suggest a link - that gender and gender inequalities matter to ageing. The five short stories viewed here are: `Dhvanyartha' by Saroj Pathak, 1There was a Message...' by Mithra Venkatraj, `Dahan' by Suchitra Bhattacharya, `Rangamma' by Madhuranthakam Narendra and `Tiny's Granny' by Ismat Chugtai. - Reproduced
Keywords: Womens studies